UK adult ADHD services in crisis - Michael C. F. Smith; Raja A. S. Mukherjee; Ulrich Müller-Sedgwick; Dietmar Hank; Peter Carpenter; Marios Adamou (BJPsych Bulletin, 2024)
The UK's services for adult attention-deficit hyperactivity disorder (ADHD) are in crisis, with demand outstripping capacity and waiting times reaching unprecedented lengths. Recognition of and treatments for ADHD have expanded over the past two decades, increasing clinical demand. This issue has been exacerbated by the COVID-19 pandemic. Despite an increase in specialist services, resource allocation has not kept pace, leading to extended waiting times. Underfunding has encouraged growth in independent providers, leading to fragmentation of service provision. Treatment delays carry a human and financial cost, imposing a burden on health, social care and the criminal justice system. A rethink of service procurement and delivery is needed, with multiple solutions on the table, including increasing funding, improving system efficiency, altering the service provision model and clinical prioritisation. However, the success of these solutions hinges on fiscal capacity and workforce issues.